USO DE UN INOCULANTE TERMOFILICO EN LA TRANSFORMACIÓN DE RESIDUOS SÓLIDOS URBANOS (RSU) - D. Rodríguez; A. Ruiz; M. Martínez-Salgado; A. Matiz (Universitas Scientiarum, 2007)
“Don Juanito” sanitary landfield, located in Villavicencio city, Colombia, is one of the most importantresearch places in organic solid waste management. This industry is developing an important alternativeof transformation and use of organic wastes, through composting process enriched with thermophilicmicrobial inoculum. The inoculum is made up of indigenous bacteria with amilolytic activity in range of114.5 UA, and proteolytic activity of 98.5 UP; these values are significant for an effective and speedygeneration of decomposed organic waste.This study evaluated a treatment in which rice husks, ruminal content, grass and 50% of organic solidresidues were mixed. A control with 55% organic solid residues as indicated in prior researches was used.Composting process was carried out within 8 weeks. Maximum temperatures of 70.8ºC in treatment and74.26ºC in control were recorded respectively. These values were recorded after the first two days ofprocessing. Resulting product was free of Salmonella spp, thermotolerant coliforms and E. coli, andshowed to have as physico-chemical characteristics: 11.13% of organic carbon, chemises 36.1%, C.I.C. of32.5 me/100g; C/N ratio of 9.66, total nitrogen 1.16%, total phosphorous 1.66%, potassium 2.3%,calcium 3.7% and magnesium 1.09%. These values nearly match those required under ICONTEC-NTC/5167 (2004).